An analysis of the refuse removal tariff setting in municipalities: a case study of City of Mutare, - Zimunya, Eugen Musabayana (Midlands State University, 2014)
The study sought to analyse the refuse removal tariff setting in Municipalities. In this study the Finance Director, middle management, employees and councillors of Mutare City Council as well as households in the high density suburbs were used as the research subjects. Data collection was mainly by way of 53 questionnaires, 7 scheduled interviews as well as Mutare City Council documentary review. The results showed that residents’ inputs were not crafted into the final budget. The Council was not educating the residents on litter reduction and waste management projects. The Finance Committee’s tariff was operating at US$2.87 and was below cost. The refuse removal tariff was not cost reflective since mark-up and other costs were not included. The majority respondents agreed on a US$8.00 charge for refuse removal. City of Mutare must establish another dumping site other than the usual Munene River which had received pollution complaints from the owners in Mozambique. The study showed that the decision makers did not have adequate time to discuss tariff setting criteria’s reports with their subordinates and the households. This study recommends the Finance Committee to be given some orientation on refuse removal tariff setting procedures and the implementation of the processes. Finally, it is also recommended that further research be undertaken in order to establish refuse removal tariff setting processes used in municipalities.